Molecular detection of Toxoplasma gondii in water samples from Scotland and a comparison between the 529bp real-time PCR and ITS1 nested PCR. (15th December 2015) - Wells, Beth; Shaw, Hannah; Innocent, Giles; Guido, Stefano; Hotchkiss, Emily; Parigi, Maria; Opsteegh, Marieke; Green, James; Gillespie, Simon; Innes, Elisabeth A.; Katzer, Frank
Abstract: Waterborne transmission of Toxoplasma gondii is a potential public health risk and there are currently no agreed optimised methods for the recovery, processing and detection of T. gondii oocysts in water samples. In this study modified methods of T. gondii oocyst recovery and DNA extraction were applied to 1427 samples collected from 147 public water supplies throughout Scotland. T. gondii DNA was detected, using real time PCR (qPCR) targeting the 529bp repeat element, in 8.79% of interpretable samples (124 out of 1411 samples). The samples which were positive for T. gondii DNA originated from a third of the sampled water sources. The samples which were positive by qPCR and some of the negative samples were reanalysed using ITS1 nested PCR (nPCR) and results compared. The 529bp qPCR was the more sensitive technique and a full analysis of assay performance, by Bayesian analysis using a Markov Chain Monte Carlo method, was completed which demonstrated the efficacy of this method for the detection of T. gondii in water samples. Graphical abstract: Highlights: Water samples (n = 1427) were collected from 147 Scottish public water supplies. Modified methods of T. gondii oocyst recovery and DNA extraction were applied. T. gondii DNA was detected in 8.79% of samples using 529bp qPCR. Nested PCR targeting the ITS1 gene was less sensitive than 529bp qPCR. Statistical analysis of 529bp qPCR confirmed it was reproducible and repeatable.